Clinical Characteristics of Pediatric Myocarditis Stratified by Left Ventricular Ejection Fraction and Factors Associated with ECMO Support - Lingzhu Huang; Jingbo Jiang; Ying Qi; Weike Ma; Xiaozhou Chen; Ping Song (Clinical Pediatrics, 2026)
Pediatric myocarditis presents with heterogeneous clinical manifestations and may progress to severe cardiac dysfunction requiring advanced life support. This retrospective study included 78 children with clinically suspected myocarditis treated between January 2021 and December 2024. Children were stratified by left ventricular ejection fraction (LVEF) at admission and further analyzed according to the use of extracorporeal membrane oxygenation (ECMO). Children with LVEF